Zimbabwean copyright law and its effectiveness in protecting composers’ intellectual property rights. - Banda, Jane (Midlands State University, 2017)
The purpose of this study is to gain insight on the Zimbabwean Copyright Law and its effectiveness in protecting music composers’ intellectual property rights. The research outlined he background to the origin of copyright law and it aimed at investigating how this copyright law has helped music composers benefit from it. The researcher used descriptive research where interview guides and questionnaires were distributed to some of the music composers registered with the Zimbabwe Music Rights Association. A Sample of music composers participated in the research and they represented the whole musicians. Random selection was used and questionnaires were distributed to music listeners and composers. The findings show that not all music listeners know and understand the copyright law and what it offers to music composers so that they benefit from their intellectual property rights. Music composers on the other hand know and understand how it has helped them in protecting their intellectual property rights. Conclusions drawn from the literature review as well as the data collected and data collected and data gathered indicate that there is need for more workshops to be done so as to educate both music listeners and composers so that they really understand the significance of copyright law.The researcher recommends that music listeners and composers should realize the effectiveness of copyright. It is therefore the researchers hope that this research will help music composers become conscious about Zimbabwean copyright law and its significance to their musical growth and protection of their intellectual.